Speech to the Representative Council of the Teachers Association of the Oxnard Union High School District - Jane Tolmach::::::
Speech made by Jane Tolmach to the Representative Council of the Teachers Association of the Oxnard Union High School District discussing her past on the Board of Trustees and the goals she has for future funding to the schools.